Effect of tricalcium aluminate and sodium aluminate on thaumasite formation in cement paste. (30th October 2020) - Jiang, Dongbing; Li, Xiangguo; Jiang, Wenguang; Li, Changjiao; Lv, Yang; Zhou, Yang
Highlights: Thaumasite-ettringite solid solution could be formed in the presence of C3 A. The formation time of thaumasite was longer than that of ettringite. Thaumasite was not found in cement paste containing NaAlO2 . The presence of AlO4 might probably restrain the formation of thaumasite. Abstract: The purpose of this paper was to study the effect of different aluminum phases on the formation of thaumasite in cement paste. In the present study, tricalcium aluminate (C3 A) and sodium aluminate (NaAlO2 ) were chosen as two kinds of aluminum phase sources. Two cement pastes were designed: one was prepared with tricalcium silicate (C3 S), calcium carbonate (CaCO3 ) and C3 A, another was prepared with C3 S and CaCO3 . Two samples were cured for 28 days and then immersed in sodium sulfate (Na2 SO4 ) solution with/without NaAlO2 at 5 °C for a certain time. The cement corrosive products were analyzed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Nuclear magnetic resonance (NMR), and Scanning electron microscope with energy dispersive spectroscopy (SEM/EDS). Results showed that thaumasite-ettringite solid solution could be formed in cement paste containing C3 A, but the formation time of thaumasite was much longer compared with that of ettringite, in agreement with the woodfordite route. In the case of using NaAlO2 as aluminum phase, ettringite was formed in the sample, while no thaumasite was formed in cement paste after being cured for 14 months. According to the analysis of 27 Al NMR, the peak of hexahedrally coordinated aluminum (AlO4 ) at 58.6 ppm was proved to be Al(OH)3, which would probably restrain the formation of thaumasite. It was indicated that the use of sodium aluminate was unfavorable for the formation of the thaumasite in cement paste.